2009
DOI: 10.1007/s11244-009-9217-1
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Size Dependence of the Acidic Property of Mesoporous Silica FSM-16

Abstract: The pore-size dependence of the acidic properties of mesoporous silica FSM-16 in the range from 1.8 to 3.8 nm was investigated with the catalysis of 2-butanol dehydration and using FTIR spectra of adsorbed pyridine. The activity was the highest for FSM-16 with a minimum pore diameter, and decreased with increasing pore size. Differences in the acid amounts of siliceous FSM-16 and the strength dependent on the pore diameter were not confirmed by FTIR characterization using pyridine as a probe molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A possible reason for the lower catalytic activity of M41-pH4.5 was the partial destruction and/or distortion of the hexagonally ordered structure that is characteristic of the parent M41. It was presumed that the regularity and/or uniformity of the pore structure could affect the intrinsic acidity of FSM-16 (Yamamoto et al, 2009). Iwamoto et al (2003) proposed that an assembly of weakly acidic OH on the uniform surface of MCM-41 may act as an effective and strong acid site.…”
Section: Catalytic Activity Of the Silica Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible reason for the lower catalytic activity of M41-pH4.5 was the partial destruction and/or distortion of the hexagonally ordered structure that is characteristic of the parent M41. It was presumed that the regularity and/or uniformity of the pore structure could affect the intrinsic acidity of FSM-16 (Yamamoto et al, 2009). Iwamoto et al (2003) proposed that an assembly of weakly acidic OH on the uniform surface of MCM-41 may act as an effective and strong acid site.…”
Section: Catalytic Activity Of the Silica Catalystsmentioning
confidence: 99%
“…Considering the above reports and the present results of the characterization and catalytic activity test, the ordered mesoporous structure seemed to be essential to great catalysis for the ODH of isobutane. The great catalytic activity of mesoporous silicas has been reported in reactions wherein the regular mesopore structures of the silica catalysts seemed to be an essential element (Ishitani and Iwamoto, 2003;Iwamoto et al, 2003;Ishitani et al, 2008;Yamamoto et al, 2009).…”
Section: Catalytic Activity Of the Silica Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar "confinement effect" has been confirmed in other catalytic systems. [67][68][69][70] The detailed reason for such an effect is still not clear. In more general terms, the pore size and wall thickness of mesoporous metal oxides have been demonstrated to influence their performance in lithium batteries 52 and chemical sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic activity for 2-butanol dehydration was found to depend on pore size of FSM-16 in the range of 1.8 to 3.8 nm (Fig. 10) 44) as for acetalization by MCM-41 49) . We have also confirmed that amorphous silicas prepared from the same raw materials as the active FSM-16 were inactive, and collapsed FSM-16 without ordered porosity was as well.…”
Section: )mentioning
confidence: 96%